Hospitalization at the end of life among nursing home residents with dementia: a systematic review - Hoffmann, Falk (BMC Palliat Care, 2019)
BACKGROUND: Half of nursing home residents (NHR) suffer from dementia. End-of-life hospitalizations are often burdensome in residents with dementia. A systematic review was conducted to study the occurrence of hospitalizations at the end of life in NHR with dementia and to compare these figures to NHR without dementia. METHODS: A systematic literature search in MEDLINE, CINAHL and Scopus was conducted in May 2018. Studies were included if they reported proportions of in-hospital deaths or hospitalizations of NHR with dementia in the last month of life. Two authors independently selected studies, extracted data, and assessed quality of studies. RESULTS: Nine hundred forty-five citations were retrieved; 13 studies were included. Overall, 7 studies reported data on in-hospital death with proportions ranging between 0% in Canada and 53.3% in the UK. Studies reporting on the last 30 days of life (n = 8) varied between 8.0% in the Netherlands and 51.3% in Germany. Two studies each assessed the influence of age and sex. There seem to be fewer end-of-life hospitalizations in older age groups. The influence of sex is inconclusive. All but one study found that at the end of life residents with dementia were hospitalized less often than those without (n = 6). CONCLUSIONS: We found large variations in end-of-life hospitalizations of NHR with dementia, probably being explained by differences between countries. The influence of sex and age might differ when compared to residents without dementia. More studies should compare NHR with dementia to those without and assess the influence of sex and age. TRIAL REGISTRATION: PROSPERO registration number CRD42018104263.